Development of male breast cancer in a patient with prostate cancer during androgen deprivation therapy. Issue 2 (11th January 2022) - Mizusawa, Hiroya; Komatsu, Akira; Mimura, Yuji; Maejima, Toshitaka
Abstract : Introduction: Male breast cancer accounts for <1% of all breast cancer. We report a patient with prostate cancer during hormone therapy who developed breast cancer. Case presentation: An 88‐year‐old male underwent androgen deprivation therapy for prostate cancer and developed an induration in the left breast 7 years after the start of treatment. After close examination, he was diagnosed with left breast cancer with lymph node metastasis. The prostate cancer was stable in a hormone‐sensitive state. Left mastectomy was performed and the pathological diagnosis was invasive ductal carcinoma. Discussion: In addition to our patient, seven patients who developed breast cancer during hormone therapy for prostate cancer were examined. Five of six patients had stage II or above, and four patients had lymph node metastases. Although local breast symptoms are frequently observed as adverse effects of hormone therapy, caution is warranted regarding male breast cancer.